Effect of Hypoxia on Adult Müller Glia Cultures - Xabier Miguel-López; Laura Prieto-López; Elena Vecino; Xandra Pereiro (Biomedicines)
Background: The retina, a light-sensitive tissue of the central nervous system that is located at the posterior part of the eye, is particularly vulnerable to alterations in oxygen levels. In various retinal diseases, such as central retinal vein occlusion, glaucoma, and diabetic retinopathy, hypoxia (a condition of low oxygen levels) is commonly observed. Müller glia, the principal glial cells in the retina, play a crucial role in supporting the metabolic needs of retinal neurons. They are also responsible for sensing oxygen levels and, in response to hypoxia, express Hypoxia-Inducible Factor 1 (HIF-1), a transcription factor that activates signaling pathways related to hypoxia. Methods: In this study, primary rat Müller glial cells were cultured and exposed to a 1% oxygen for 72 h. Following this, immunohistochemical assays were conducted to assess the effects of hypoxia on various parameters, including HIF-1α expression, cell survival, Müller glia-specific markers (CRALBP and GS), gliosis (GFAP expression), apoptosis (caspase-3 expression), cell proliferation (Ki-67 expression), and metabolic stress (indicated by the number of mitochondria per cell). Results: Under hypoxic conditions, a decrease in Müller glial survival and proliferation was observed. Conversely, there was an increase in HIF-1α expression, GFAP expression, caspase-3-positive cells, and the number of mitochondria per cell. However, no significant changes were noted in the expression of the Müller glial markers GS and CRALBP. Conclusions: In conclusion, hypoxia resulted in reduced proliferation and survival of Müller glial cells, primarily due to increased apoptosis and heightened metabolic stress.